(untitled) (International journal of medical sciences, 2026)
The use of biological technologies is gaining significant importance in modern surgery and regenerative medicine. In recent years, autologous biomaterials based on the patient's own blood components have become widely used in surgical practice. Among these, Platelet Rich Fibrin (PRF) technology holds particular scientific and practical value, as a natural biomaterial rich in platelets, fibrin, and leukocytes that accelerates tissue regeneration. PRF technology is an effective method for rapid wound healing, reducing inflammatory processes, preventing postoperative complications, and shortening rehabilitation periods. This article provides an in-depth analysis of the biological foundations of PRF technology, its application in surgical practice, clinical effectiveness, and research results. The study was conducted based on local and foreign scientific sources, highlighting the prospects of PRF technology in surgery.